2006
DOI: 10.1534/genetics.105.054429
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Physical Mapping of the Apospory-Specific Genomic Region in Two Apomictic Grasses: Pennisetum squamulatum and Cenchrus ciliaris

Abstract: In gametophytic apomicts of the aposporous type, each cell of the embryo sac is genetically identical to somatic cells of the ovule because they are products of mitosis, not of meiosis. The egg of the aposporous embryo sac follows parthenogenetic development into an embryo; therefore, uniform progeny result even from heterozygous plants, a trait that would be valuable for many crop species. Attempts to introgress apomixis from wild relatives into major crops through traditional breeding have been hindered by l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
36
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 44 publications
(36 citation statements)
references
References 36 publications
0
36
0
Order By: Relevance
“…Given the hemizygosity, as well as genetic data suggesting that the region responsible for apospory may be physically large, the term ASGR (for apospory-specific genomic region) was coined to describe the locus in Pennisetum/ Cenchrus. Ninety-nine bacterial artificial chromosome (BAC) clones containing molecular markers (SCARs, RFLPs, and AFLPs) showing total genetic linkage to the aposporous phenotype have been identified from BAC libraries constructed from the apomictic polyhaploid line MS228-20 and the apomictic Cenchrus ciliaris line B-12-9 (Roche et al, 2002;Akiyama et al, 2004;Goel et al, 2006). These BACs will be referred to as ASGR-BACs.…”
mentioning
confidence: 99%
“…Given the hemizygosity, as well as genetic data suggesting that the region responsible for apospory may be physically large, the term ASGR (for apospory-specific genomic region) was coined to describe the locus in Pennisetum/ Cenchrus. Ninety-nine bacterial artificial chromosome (BAC) clones containing molecular markers (SCARs, RFLPs, and AFLPs) showing total genetic linkage to the aposporous phenotype have been identified from BAC libraries constructed from the apomictic polyhaploid line MS228-20 and the apomictic Cenchrus ciliaris line B-12-9 (Roche et al, 2002;Akiyama et al, 2004;Goel et al, 2006). These BACs will be referred to as ASGR-BACs.…”
mentioning
confidence: 99%
“…Analysis of mRNA tags of apomictic and sexual ovules in the Boechera holboellii complex implicate polyploid gene dosage in the expression of asexual seed formation, and support hypotheses of deregulation of the sexual pathway (Sharbel et al, 2009). Physical mapping of the apospory-specific genomic region (ASGR) in two apomictic grasses, Pennisetum squamulatum and Cenchrus ciliaris, showed that the ASGR appears to be maintained as a haplotype even though its position in the genome can be variable (Goel et al, 2006), and genetic mapping of the ASGR in P. squamulatum using retrotransposon-based molecular markers is problematic (Huo et al, 2009).…”
Section: Introductionmentioning
confidence: 66%
“…Several genomic studies on gametophytic apomixis in some grass species have been published (Akiyama et al 2004, Ebina et al 2005, Goel et al 2006. In these studies, the construction of high-density genetic linkage maps flanking the apomixis locus and isolation of BAC clones containing markers linked to the apomixis locus were performed, but positional cloning of the gene responsible has not been achieved due to the occurrence of recombination suppression in the flanking region (OziasAkins and van Dijk 2007).…”
Section: Discussionmentioning
confidence: 99%